The Effect of Quiz Case Game in Kemp's Model on Creative Thinking and Learning Motivation - Puput; Hartoyo , Agung; Mirza, Ade; Hamdani; Fitriawan, Dona (Jurnal Riset Pendidikan Matematika, 2025)
This study examines the effect of the Quiz Case game in the Kemp model on students' creative thinking and learning motivation. Using a Quasi-Experimental Design with Nonequivalent (Pretest-Posttest) Control Group Design, 66 students were divided into experimental and control groups (33 each) through purposive sampling. The experimental class used the Quiz Case game, while the control class used Matching Pairs. Data were collected via tests and questionnaires, analyzed with N-gain, Mann-Whitney U, effect size, and Spearman correlation. The experimental class showed higher creative thinking improvement (N-gain 0.68; 68.97%) than the control (0.30; 30.61%). Learning motivation improvement was similar in both classes (0.62 vs. 0.59). Mann-Whitney U indicated significant differences in creative thinking (sig. = 0.000) but not motivation (sig. = 0.346). Spearman correlation showed a strong relationship (r = 0.756). Thus, the Quiz Case game effectively enhances creative thinking and learning motivation.